Assessment of allergy knowledge among the Palestinian community: A cross-sectional study - Maha Rabayaa; Mustafa Ghanim; Malik Alqub; Mohammad Abuawad; Majdi Dwikat; Samar Alkhaldi; Haneen Badawi; Johnny Amer (PLoS ONE, 2025)
Introduction Allergy is a form of chronic illness with an increasing prevalence globally. Adequate knowledge among the community about the causes, symptoms, and treatment of allergy is crucial in preventing the associated life-threatening complications. Limited research has been conducted in Palestine regarding this health priority. The current study aimed to assess the Palestinian community’s level of knowledge regarding allergy. Methods An observational cross-sectional study was conducted using an online questionnaire targeting Palestinians aged 18 years and older between 1 June 2024 and 26 January 2025. The questionnaire gathered demographic information about the participants and assessed their knowledge level concerning allergy. Results A total of 1002 participants were included in the study. The mean age of the participants was 30.33 years. 66.1% of the participants were females, 60.2% were unmarried, 60.1% had possessed a bachelor’s degree, 63.1% had a personal history of allergy, and 82% reported knowing of someone with allergies. The mean knowledge score about allergies was 5.4 out of 10, with over half of the participants having an average level of knowledge (4–6). The knowledge score about allergies was significantly different based on the participants’ sex, marital status, place of residence, educational level, and occupation (p-value <0.001). Conclusion The Palestinians’ knowledge of allergy is considered good regarding its common causes and symptoms. However, there is still inadequate knowledge about the treatment of allergy and its less common causes. The community awareness of allergy should be improved through targeted campaigns and brochures aimed at achieving earlier diagnosis and proper management to prevent the development of life-threatening complications.